Research on the Middle Palaeolithic in Dalmatia, Croatia - Karavanić, Ivor (Array, 2000)
The only systematically excavated site in Dalmatia, with clear and homogenous Mousterian stratigraphic context suitable for absolute dating, is Mujina Pećina. The cave is about 10 m deep and 8 m wide. It is situated north of Trogir and west from Split in typical karstic terrain. Here research aims to provide a framework for the interpretation of environmental conditions and Neanderthal adaptations in Dalmatia, and practical training for undergraduate and postgraduate students.